Financial Constraints and Student Consumption: Prioritizing Economic Efficiency Over Nutritional Balance - Erdani, Yuliadi; Athoriq, Alif Yasir; Lubis, Abrar Wahid; Hanifah, Anna; Ijazilah, Aqila Bihar (JISTech (Journal of Islamic Science and Technology), 2025)
This study investigates students' food consumption patterns under financial constraints. A quantitative survey was conducted using a Likert-scale questionnaire distributed to 42 students of Politeknik Manufaktur Bandung. Data were examined using descriptive statistics, including frequency distribution and mean scores, complemented by inferential analysis (Kruskal-Wallis test and Pearson correlation). The findings indicate that promotional availability and price are the most influential factors in food selection, with mean scores of 4.45 and 4.38, respectively. Accessibility and practicality follow as important considerations. Conversely, nutritional value and taste rank lower in priority among the respondents. Furthermore, the inferential analysis shows no statistically significant relationship between bringing meals from home and self-reported energy levels (p = 0.789). These results suggest that students tend to prioritize economic efficiency over nutritional aspects when managing limited financial resources. Greater awareness and education regarding healthy and affordable food choices are recommended to support better dietary habits among students.